Simulation-Based Abdominal Ultrasound Training – A Systematic Review - Østergaard, M. L.; Ewertsen, C.; Konge, L.; Albrecht-Beste, E.; Bachmann Nielsen, M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: The aim is to provide a complete overview of the different simulation-based training options for abdominal ultrasound and to explore the evidence of their effect.Materials and Methods: This systematic review was performed according to the PRISMA guidelines and Medline, Embase, Web of Science, and the Cochrane Library was searched. Articles were divided into three categories based on study design (randomized controlled trials, before-and-after studies and descriptive studies) and assessed for level of evidence using the Oxford Centre for Evidence Based Medicine (OCEBM) system and for bias using the Cochrane Collaboration risk of bias assessment tool.Results: Seventeen studies were included in the analysis: four randomized controlled trials, eight before-and-after studies with pre- and post-test evaluations, and five descriptive studies. No studies scored the highest level of evidence, and 14 had the lowest level. Bias was high for 11 studies, low for four, and unclear for two. No studies used a test with established evidence of validity or examined the correlation between obtained skills on the simulators and real-life clinical skills. Only one study used blinded assessors.Conclusion: The included studies were heterogeneous in the choice of simulator, study design, participants, and outcome measures, and the level of evidence for effect was inadequate. In all studies simulation training was equally or more beneficial than other instructions or no instructions. Study designs had significant built-in bias and confounding issues; therefore, further research should be based on randomized controlled trials using tests with validity evidence and blinded assessors.
Keywords: ultrasound; education; abdomen; simulation